Wireless Closed-Loop Optical Regulation System for Seizure Detection and Suppression In Vivo - Li, Yamin; Xu, Shengwei; Wang, Yang; Duan, Yiming; Jia, Qianli; Xie, Jingyu; Yang, Xiaowei; Wang, Yiding; Dai, Yuchuan; Yang, Gucheng; Yuan, Miao; Wu, Xiaoting; et al. (Frontiers in Nanotechnology, 2022)
There are about 50 million people with epilepsy worldwide, even about 25% of whom can't be effectively controlled by drug or surgical treatment. A wireless closed-loop system for epilepsy detection and suppression is proposed in this paper. The system is composed of implantable optrode, wireless recording, wireless energy supply, and control module. The system can monitor brain electrical activity in real-time. When the seizures are recognized, the optrode will be turned on. The preset photosensitive caged compounds is activated to inhibit the seizure. While seizure is inhibited or ended, the optrode will be turned off. The method demonstrates a practical wireless close-loop epilepsy therapy system.